EXTRAGENITAL LICHEN SCLEROSUS IN A CHILD WITH A GOOD RESPONSE TO COLCHICINE - Juliana Salvini Barbosa Martins da Fonseca; Aline Godinho Ferreira Silva; Mariana Gardone Guimarães; Paôlla Alves de Faria; Fred Bernardes Filho (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Lichen sclerosis is a chronic inflammatory disease of multifactorial origin involving genetic, physiological and environmental. Usually affects women between 50-60 years old, in the genital form. The pathology is uncommon in children in the extragenital form. It´s accepted as na autoimune disorder, but the mechanism remains unclear. The case report presented the flame extragenital attention as the variant form, displaying an unusual location to be affected.We report the case of a child with extragenital form with an unusual location, femoral region. Patient made use of other medications, but had clinical improvement after the use of topical colchicine. This drug has good absorption topically and has the capacity to interrupt the mitoses of the cell. Besides that have an anti-inflammatory effect reducing mobility, adhesion and chemotaxis of polimorphonuclear cells, on the desgranulacion of lysossomes.